FRI0248 Predictors of Disability in Systemic Sclerosis: A Study from The Desscipher Project. (15th July 2016) - Jaeger, V.K.; Abignano, G.; Allanore, Y.; Avouac, J.; Czirják, L.; Del Galdo, F.; Denton, C.; Distler, O.; Frerix, M.; Guiducci, S.; Huscher, D.; Lόránd, V.; et al.
Abstract : Background: Systemic sclerosis (SSc) can greatly impact the patients' quality of life due to the multisystem manifestations. The health assessment questionnaire (HAQ) is one of the most commonly used measures of disability in musculoskeletal disorders and was extended to form the scleroderma HAQ (SHAQ), a more disease-specific disability scale that incorporates the HAQ and the 5 SHAQ-visual analogue scales (VAS) into one score. Objectives: This study aims to identify predictors of disability in SSc by means of the SHAQ. Methods: Patients from the DeSScipher cohort were included in the analysis if they had at least one complete SHAQ recorded, fulfilled either the 1980 ACR or the 2013 ACR/EULAR criteria for SSc and were above 18 years of age. Multiple linear regression analysis was used to assess the combined effect of factors possibly associated with disability. Variables included in the model were defined a priori. Results: 813 patients had one complete SHAQ recorded between June 2013 and January 2016 (34.1% of all patients followed in the DeSScipher cohort). Of these, 12% fulfilled only the 2013 ACR/EULAR criteria, 2% fulfilled only the 1980 ACR criteria and 86% fulfilled both, the median age was 58 years (IQR 49–67) and 15% were male. 26% of the patients were in the diffuse SSc subset, 56% in the limited and 18% had SSc sine sclerosis. The patients had a median SHAQ score of 0.79 (IQR 0.28–1.31) and a median HAQ score of 0.88 (IQR 0.25–1.5). The medians of the five VASs included in the SHAQ were (in order of the VAS magnitude): overall disease severity (30, IQR 10–51), Raynaud's phenomenon (21, IQR 3–50), pulmonary symptoms (10, IQR 1–40), gastrointestinal symptoms (6, IQR 1–31) and digital ulcers (2, IQR 1–30). 60% of the patients were in the lowest SHAQ category (score of 0 to 1) which is regarded as "mild to moderate difficulty", 34% in the category regarded as "moderate to severe disability" (score of 1 to 2) and 6% in the category regarded as "severe to very severe disability" (score of 2 to 3). In multiple linear regression, the main factors associated with high SHAQ scores were dyspnoea (NYHA-stage 4 (β=0.67), 3 (β=0.59) and 2 (β=0.18; all vs. stage 1), fibromyalgia (β=0.42), muscle weakness (β=0.25), current digital ulcers (β=0.20) and gastrointestinal symptoms (oesophageal symptoms, β=0.18; stomach symptoms, β=0.14; intestinal symptoms, β=0.14; figure ). Conclusions: Patients perceive dyspnoea, pain, digital ulcers, muscle weakness and gastrointestinal symptoms as the main factors driving their level of disability. Acknowledgement: The DeSScipher project was funded by the European Community's Framework Programme 7 (FP7-HEALTH-2012.2.4.4–2-Observational trials in rare diseases) under grant agreement N° 305495. We acknowledge the contribution of the following EUSTAR centres: Moscow(78), Padova(31), Istanbul(133), Wuppertal(192), Monserrato(142), Roma(94), Cologne(44), Cluj-Napoca(16), Ancona(34), Iasi(162), Frankfurt(124). Disclosure of Interest: None declared